Legislative Shortcomings in the Crime of Trafficking in Persons Under the Law 09-01 - Atamnia, Kawser (Journal of Legal Studies and Researches, 2022)
Algeria took the initiative to criminalize trafficking in persons, In order to determine the adequacy of this criminal policy , we decided to study the most important legal requirements in both the criminalization and punishment policy and to clarify the legislative deficiencies in it in order to strengthen the fight against trafficking in persons.